Auditory demonstrations. - Houtsma, A. J. M., ....-; Rossing, Thomas D., 1929-; Wagenaars, W. M., ....- (Eindhoven : Institute for Perception Research, 1987)
1. Frequency analysis and critical bands
2. Sound pressure, power, loudness
3. Masking
4. Pitch
5. Timbre
6. Beats, combination tones, distortion, echoes
7. Binaural effects
Keywords: Auditieve perceptie